Black entrepreneurship and DEI: Profiles and challenges of African descendant entrepreneurs within the Portuguese ecosystem - Foá, C. (Social Inclusion, 2025)
Diversity, equity, and inclusion (DEI) are essential for creating healthy and competitive innovation ecosystems where individuals and organisations thrive through equal access to resources and opportunities. Based on the principles of the European Pillar of Social Rights (EPSR) and the National Entrepreneurial Context Index (NECI), this article seeks to identify the personal and business profiles of African descendant entrepreneurs in Portugal and place their experiences within the understudied national ecosystem and its stakeholders. The research examines socio‐demographic patterns, entrepreneurial trajectories, and business dynamics through a mixed‐methods approach spanning three phases: stakeholder identification and netnography, an online survey of 200 entrepreneurs, and five focus groups with 40 stakeholders. Most entrepreneurs are young, educated, and driven by the desire for independence, solving community problems, and sustainable development. However, their start‐ups are typically in early stages, with limited focus on digitalisation and technological innovation, often emerging from strategies of emancipation and resilience against labour market disparities and work–life imbalance. Support received remains significantly below the national average—particularly in acceleration, incubation, and access to traditional funding—with notable disparities based on origins and gender. Structural inequalities persist and mainly affect PALOP women. Stakeholders’ DEI efforts and influence on Black entrepreneurship vary across socio‐political, market, and community ecosystem dimensions. Findings reveal gaps in entrepreneurs’ digital and business literacy and their underrepresentation in decision‐making roles within stakeholders’ bodies. Conclusions emphasise the need for greater visibility of Black entrepreneurship experiences, inclusive governance, and capacity‐building tailored to different stages of business development rather than target groups, along with stronger collaboration between entrepreneurial support organisations (ESOs).